Pengaruh Teknologi Informasi Terhadap Kinerja Perusahaan: Kejelasan Peran Sebagai variabel Moderating (Studi Empiris BPR Di Kabupaten Banyumas - Dona Primasari (Universitas Ahmad Dahlan, 2012)
The main objective of this study is to examine the influence of information technology and role clarity to corporate performance. Role clarity as an moderating variable. This research represents the empirical test which used sensus sampling technics in data collection. Data were collected using a survey 120 respondens. Data was analyzed by SPSS Ver 18. The result found that received one hypothesis and rejected the other.